Case Report: Diagnostic difficulties, treatment, and association of the MEFV E148Q variant in a patient with PASH syndrome - Qin, Qianfeng; Cao, Cunwei; Liang, Jiarong; Li, Bingkun; Su, Jiaguang (Frontiers in Medicine, 2025)
BackgroundPASH syndrome is a rare autoinflammatory disorder characterized primarily by pyoderma gangrenosum, acne, and suppurative hidradenitis. It is frequently misdiagnosed or underdiagnosed due to its diverse clinical manifestations. PASH syndrome is considered a polygenic autoinflammatory disease associated with multiple gene variants, among which MEFV variants may play a significant role. This case report describes a PASH syndrome patient with the MEFV variant (NM_000243.3.442G > C; p.Glu148Gln). The E148Q variant appears with high frequency as a homozygote in the gnomAD database, and its pathogenicity remains controversial.Case presentationThis case report describes a Chinese male patient with PASH syndrome who initially presented with severe acne and suppurative hidradenitis that were unresponsive to conventional therapy, subsequently developing pyoderma gangrenosum, leading to the diagnosis of PASH syndrome. Whole-exome sequencing performed during the diagnostic workup revealed the MEFV gene variant (p.E148Q). Treatment with adalimumab ultimately achieved favorable therapeutic outcomes.ConclusionThis case report represents the first documentation of a PASH syndrome patient carrying the homozygous E148Q variant. Adalimumab demonstrated good therapeutic efficacy; however, disease recurrence occurred due to poor medication adherence, highlighting the importance of long-term management. The pathogenicity of E148Q alone is relatively weak and likely depends on polygenic accumulation or epigenetic dysregulation. It may contribute to disease pathogenesis through a “variant load” mechanism in conjunction with ethnic differences and other genetic or environmental factors.